Getting comfortable with "comfort feeding": An exploration of legal and ethical aspects of the Australian speech-language pathologist's role in palliative dysphagia care. (4th May 2018) - Kelly, Katherine; Cumming, Steven; Kenny, Belinda; Smith-Merry, Jennifer; Bogaardt, Hans
Abstract: Purpose : With an ageing population, speech-language pathologists (SLPs) can expect to encounter legal and ethical challenges associated with palliative and end-of-life care more frequently. An awareness of the medico-legal and ethical framework for palliative dysphagia management will better equip SLPs to work effectively in this area. Method : This narrative review examines a range of legislation, legal, ethical and SLP literature that is currently available to orient SLPs to legal and ethical palliative dysphagia management in the Australian context. Result : Relevant legal and ethical considerations in palliative and end-of-life care are described. Conclusion : SLPs have a role in palliative dysphagia management, however, this can involve unique legal and ethical challenges. The legal position on provision and cessation of nutrition and hydration differs between Australian States and Territories. Decisions by the courts have established a body of relevant case law. This article introduces SLPs to some of the important considerations for legal and ethical palliative care, but is not intended to be directive. SLPs are encouraged to explore their local options for ethical and medico-legal guidance. It is hoped that increasing SLPs awareness of many of the concepts discussed in this article enhances the provision of high-quality patient-centred care.